Association between mid‐ and late‐ life cardiometabolic multimorbidity and dementia risk: a nationwide twin study. (20th December 2022) - Dove, Abigail; Guo, Jie; Fastbom, Johan; Marseglia, Anna; Vetrano, Davide Liborio; Pedersen, Nancy L.; Xu, Weili
Abstract: Background: Cardiometabolic diseases (CMDs) have been linked to increased dementia risk, but their combined impact on dementia and its major subtypes remains unknown. We aimed to examine the association between mid‐ and late‐ life onset cardiometabolic multimorbidity with risk of dementia, Alzheimer's disease (AD), and vascular dementia (VaD), and to explore whether genetic background contributes to this association. Method: Within the Swedish Twin Registry, 17, 387 dementia‐free individuals aged ≥60 were followed for up to 18 years to detect incident dementia. Dementia (including AD and VaD) was identified based medical records from the National Patient Registry (NPR) and the Swedish Cause of Death Register. CMDs (including type 2 diabetes, heart disease, and stroke) and age at onset (mid‐life [<60 years] vs. late life [≥60 years]) were ascertained from NPR records. CMD multimorbidity was defined as the presence of ≥2 co‐morbid CMDs. Data were analyzed using two strategies: 1) unmatched analysis using Cox models conducted among all twin individuals (to assess the CMD‐dementia association); and 2) co‐twin matched analysis using Cox models stratified by zygosity in dementia‐discordant pairs (to assess the role of genetics in this association). Result: Of all participants, 3, 176 (18.3%) had a single CMD and 789 (4.5%) had CMD multimorbidity at baseline. During the follow‐up, 2, 494 participants developed dementia (including 817 AD and 515 VaD cases). The hazards ratios (HRs, 95% CIs [confidence intervals]) of dementia were 1.36 (1.23‐1.51) (1.23, 1.03‐1.49 for AD and 1.53, 1.23‐1.89 for VaD) for a single CMD, and 1.82 (1.48‐2.23) (1.39, 0.93‐2.09 for AD and 2.41, 1.64‐3.55 for VaD) for CMD multimorbidity. In stratified analysis, the HRs of the associations between mid‐ and late‐ life onset CMD multimorbidity and dementia were 2.47 (1.43‐4.28) and 1.72 (1.39‐2.14), respectively. In co‐twin matched analysis, the CMD‐dementia association remained significant in dizygotic twins (n = 544; HR 1.68, 95% CI 1.26‐2.39), but was greatly attenuated among monozygotic twins (n = 102; 0.84, 0.42‐1.65) (p = 0.045 for interaction). Conclusion: Cardiometabolic multimorbidity, particularly in mid‐life, is associated with an increased risk of dementia, AD, and VaD after age 60. Genetic background appears to underpin the CMD‐dementia association.